ANALISIS YURIDIS PERKAWINAN BEDA AGAMA MENURUT SURAT EDARAN MAHKAMAH AGUNG NOMOR 2 TAHUN 2023 - NIM. A1012201142, CRISTINE CLAUDIA ANGELIE (Jurnal Fatwa Hukum, 2024)
Abstrac The validity of a marriage is regulated in article 2 paragraph 1 which states that a marriage is valid if it is carried out according to each religion, so that marriages between different religions cannot be carried out in Indonesia. However, in reality there are still judges who declare it valid and grant marriages between different religions even after the issuance of the Letter. Supreme Court Circular No. 2 in 2023.The method used in this research is normative law with a statutory approach. This research is descriptive analytical in nature. The data sources for this research are secondary and tertiary data. Meanwhile, the legal materials used are primary, secondary and tertiary legal materials. Data collection was carried out by literature study. This research analysis was carried out using qualitative techniques.The results of this research are that with the Supreme Court Circular it should be clear that interfaith marriages cannot be carried out in Indonesia because they are not in accordance with existing religious norms in Indonesia and Law No. 1 of 1974. And everyone is obliged to comply with the restrictions imposed has been stipulated by Law No.1 of 1974 and Supreme Court Circular No. 2 in 2023.Keywords: Marriage, Different Religions, Supreme Court Circular No. 2 in 2023 Abstrak Sahnya suatu perkawinan diatur dalam pasal 2 ayat 1 yang menyatakan bahwa perkawinan adalah sah apabila dilakukan menurut masing-masing agama, sehingga perkawinan beda tidak dapat dilakukan di Indonesia, Namun pada kenyataannya masih ada hakim yang menyatakan sah dan mengabulkan perkawinan beda agama bahkan setelah dikeluarkannya Surat Edaran Mahkamah Agung No. 2 tahun 2023.Metode yang dilakukan dalam penelitian ini adalah hukum normatif dengan penndekatan Perundang-Undangan. Penelitian ini bersifat deskriptif analitik. Sumber data dari penelitian ini adalah data sekunder dan tersier. Sedangkan bahan hukum yang digunakan adalah bahan hukum primer, sekunder, dan tersier. Pengumpulan data dilakukan dengan studi kepustakaan. Analisis penelitian ini dilakukan dengan teknik kualitatif.Hasil penelitian ini adalah Dengan adanya Surat Edaran Mahkamah Agung seharusnya telah jelas bahwa perkawinan beda agama tidak dapat dilakukan di Indonesia karena tidak sesuai dengan norma agama yang ada di Indonesia dan Undang-Undang No.1 tahun 1974, Dan setiap orang wajib tunduk kepada pembatasan yang telah ditetapkan oleh Undang-Undang No.1 tahun 1974 dan Surat Edaran Mahkamah Agung No. 2 tahun 2023.Kata Kunci : Perkawinan, Beda Agama, Surat Edaran Mahkamah Agung No. 2 tahun 2023